2009
DOI: 10.1097/coc.0b013e31819380a8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of T4 Locally Advanced Head and Neck Cancers With Soft Tissue Invasion or Bone and Cartilage Invasion

Abstract: This study suggests similar outcomes for CRT or resection followed up with chemoradiotherapy for patients with locally advanced SCCHN with BCI. Concurrent CRT may be viable alternative to upfront resection in these patients. Further studies should be performed to validate these provocative findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…If these clinically overstaged T4 patients had been treated with chemoradiation therapy, one could have anticipated local control and functional outcomes similar to patients with T3 disease treated with chemoradiation. To complicate matters, several recently published retrospective reports suggest that patients with cartilage invasion can successfully be treated in a nonsurgical manner [19,20]. Although the extent of cartilage invasion was not specifically quantified in these studies, the findings are nonetheless provocative.…”
Section: B LI M Bobinski R Gandour-edwards Et Almentioning
confidence: 68%
See 1 more Smart Citation
“…If these clinically overstaged T4 patients had been treated with chemoradiation therapy, one could have anticipated local control and functional outcomes similar to patients with T3 disease treated with chemoradiation. To complicate matters, several recently published retrospective reports suggest that patients with cartilage invasion can successfully be treated in a nonsurgical manner [19,20]. Although the extent of cartilage invasion was not specifically quantified in these studies, the findings are nonetheless provocative.…”
Section: B LI M Bobinski R Gandour-edwards Et Almentioning
confidence: 68%
“…They showed local regional control, disease-free survival and laryngectomyfree survival similar to the results from T3 patients treated in RTOG 9111. In another retrospective study, Do et al [20] showed similar local regional control rates between patients with cartilage invasion treated with definitive chemoradiation therapy or surgery followed by chemoradiation. Large prospective trials are needed to test the Figure 1.…”
Section: B LI M Bobinski R Gandour-edwards Et Almentioning
confidence: 93%
“…Literature on larynx preservation protocols is very heterogeneous including T1 and T2 LC or other locations of head and neck cancer, resulting in biased outcomes. Studying “advanced LC” based on staging (stage 3 and 4) means to include T1N2M0 LC cases in the same category as T4N0M0 cases for example. This can lead to significant results bias.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies are comparing survival after total laryngectomy (TL) versus OPPs in advanced LC cases to reconsider the conclusions of the VA and RTOG studies . Most studies published include different stages (T3, T4, N0, N+) of LC, with sometimes non‐LC cases (hypopharynx or oral cavity) with all the prognostic divergence . More studies are needed, with homogeneous categories of patients, to evaluate survival associated with surgery or preservation protocols and determine the most appropriate treatment modality that gives the highest survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Do et al [10] retrospectively analyzed 101 patients with stage T4 head and neck cancers treated with definitive RT or resection, from several centers associated with the University of California Davis. Subset analysis of the CRT group found no differences in LC (50% and 56% at 5 years, respectively) or OS in 26 patients with bone and/or cartilage invasion compared to 42 patients with other T4 criteria.…”
Section: Discussionmentioning
confidence: 99%